Chromosome 6p SNP microhaplotypes and IgG3 levels in hemochromatosis probands with HFE p.C282Y homozygosity - Barton, JC (2020)
Subnormal IgG1 or IgG3 levels occurred in 30% of hemochromatosis probands with HFE p.C282Y homozygosity and were concordant in HLA-identical siblings. We sought to identify factors associated with IgG subclasses in Alabama probands with p.C282Y homozygosity evaluated for 500 kb microhaplotypes AAT and GGG defined by SNPs in chromosome 6p genes PGBD1, ZNF193, and ZNF165. In regressions on IgG subclasses, we used: age; sex; GGG (dichotomous); iron removed to achieve depletion; CD8+ T-lymphocytes; and other IgG subclasses. Among 49 probands, AAT and GGG occurred in 95.9% and 16.3%, respectively. Thirteen probands (26.5%) had subnormal IgG1; 11 probands (22.4%) had subnormal IgG3. Mean IgG3 was higher in probands with than without GGG (75 mg/dL [95% confidence interval 63, 89] vs. 58 mg/dL [49, 71], respectively; p = 0.0321). Regression on IgG3 revealed: GGG positivity (p = 0.0106); and IgG1 (p = 0.0015). In a replication cohort of 22 Portugal probands with p.C282Y homozygosity, mean IgG3 was higher in probands with than without GGG (46 ± 16 vs. 31 ± 12 mg/dL, respectively; p = 0.0410). We conclude that mean IgG3 levels are higher in hemochromatosis probands with p.C282Y homozygosity with chromosome 6p microhaplotype GGG than in probands homozygous for microhaplotype AAT.